D4N2024 Presentation Showcase – Thematic Session 2b: Natural and built food environments - Karunanayaka, Madusha; Wadhwa, Rajni; Perera, Thushanthi; Ganpule-Rao, Anjali; Bi, Afrin Zainab; Shah, Nadia; Madurawala, Sunimalee; Scott, Samuel P.; Tahsin, Mariha (International Food Policy Research Institute, 2024)
D4N2024 Presentation Showcase – Thematic Session 2b: Natural and built food environments